Regional Pro Bon Conference Held at Hilton Hotel - Watkins, Howard::::::::: (1989)
Justice Hollis Best speaking at lectern: seated Frank D. Winston, State Senator Ken Maddy, Randi Saul-Olson and Glee Ewell